Problems and Adaptive Pedagogical Strategies for PAI Learning in the Merdeka Curriculum Era at SDN Kutorejo II Pandaan, Pasuruan Regency - Abdul Mukhlis (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to analyze the problems and reconstruct adaptive pedagogical strategies in Islamic Religious Education (PAI) learning based on the Independent Curriculum at SDN Kutorejo II Pandaan, Pasuruan Regency. The research uses a qualitative approach with a case study design. Data were collected through in-depth interviews, classroom observations, and documentation, and then analyzed through data condensation, data presentation, and verification. The results of the study indicate that the main problems lie in the limited pedagogical competence of teachers in implementing differentiated learning, weaknesses in diagnostic and formative assessments, and minimal integration of technology. On the other hand, adaptive dynamics were found in the form of teachers' efforts to use group discussions, open-ended questions, and activity-based learning, although these efforts were not yet consistent and systematic. Based on these findings, this study reconstructs an adaptive pedagogical strategy that includes strengthening learning differentiation, optimizing formative assessment, contextual integration of technology, and developing dialogical pedagogical interactions. This study has implications for the importance of strengthening teachers' capacity through practice-based training as well as school system support that encourages learning innovation. Thus, this study contributes to the development of an adaptive, contextual, and curriculum-relevant Islamic education (PAI) learning model in accordance with the demands of the Independent Curriculum.